NOVEL APPROACHES IN TOURISM DIGITALIZATION – STRATEGIES FOR A POST COVID - 19 WORLD - TEODOROV, Alexandru Valentin; PARTECA, Mihaela; HARBA, Jaqueline Nathalie; ABDALLAH, Awatef (Revista de turism - studii și cercetări în turism, 2021)
The SARS-CoV-2 pandemic has caused major damage to the tourism industry globally, many tour operators and agencies being forced to close down their businesses. It is no secret that the restrictions and fear of getting ill have been a deterrent when it comes to traveling abroad. However, in spite of all the damage it has caused, the COVID-19 crisis has also pushed the industry to digitalize more than ever been before. In this sense, one must regard technological advancements with a keen eye and observe the factors that can ease the access of travelers, as well as how these advancements facilitate the further development of the tourism industry. The digital transformation of tourism will not only help those that want to travel during a pandemic and are afraid to do so, but also those that are less mobile; this is an area that has not been explored up to this point. The digitalization of tourism can create a revolution when it comes to the mobility of the less mobile, offering travel opportunities for individuals with certain disabilities, or people that are unable to physically travel, because of a variety of reasons. In the given context, the present paper aims to observe the technological advancements and create a comparison between them in order to explore the best alternatives that will further develop the tourism industry in the following years, making travel, under different shapes or forms, accessible to all people, regardless of their degree of mobility.